Highly Nonlinear and Birefringent Spiral Photonic Crystal Fiber. (11th June 2014) - Revathi, S.; Inbathini, Srinivasa Rao; Saifudeen, Rizwan Ali
Abstract : We propose and design a spiral photonic crystal fiber with elliptical air holes for achieving high birefringence, large nonlinearity, and negative dispersion. The structure is designed using chalcogenide glass (As2 S3 ) for different ellipticity ratios of air holes in the cladding and the effect on various properties is observed. The proposed structure has birefringence of the order 10 −2, nonlinearity of 26739.42 W −1 m −1, and dispersion of −1136.69 at 0.85 μ m. An accurate numerical approach based on finite element method is used for the design and simulation of the structure. Due to high birefringence and negative dispersion, the proposed structure can be used for polarization control and dispersion compensation, respectively.